PENGARUH PENAMBAHAN EKSTRAK TEH HIJAU (Camellia sinensis) DALAM BAHAN PENGENCER KUNING TELUR SITRAT TERHADAP KUALITAS SPERMATOZOA DOMBA SAPUDI YANG DISIMPAN PADA SUHU DINGIN - Khoirunnisa, Itrah; Susilowati, Suherni; Maslachah, Lilik; Suprayogi, Tri Wahyu; Kurnijasanti, Rochmah; Ratnani, Hermin (Universitas Airlangga, 2019)
The purpose of this research was determine the effect and the best concentration of greentea extract in egg yolk citrate diluent for quality Sapudi sheep spermatozoa were measured in motility, viability and intact plasma membrane that was stored on cold temperature. The semen was devided into four groups : egg yolk citrate diluent, 0,05 % green tea extract in egg yolk citrate diluent, 0,1 % green tea extract in egg yolk citrate diluent and 0,15 % green tea extract in egg yolk citrate diluent. Spermatozoa quality was observed day 1, day 2, day 3, day 4 and day 5 after diluent. The data obtained was analyzed with the analysis of variance (ANOVA), followed by multiple range test duncan. The result showed that the higest precentage of motility, viability and intact plasma membran were obtained from 0,05 % green tea extract in egg yolk citrate diluent for 1 day of storage which were 85.83 ± 3.76, 91.16 ± 2.13 and 66.83 ± 6.49. The lowest precentage of motility, viability and intact plasma membrane were obtained from egg yolk citrate diluent for 5 day of storage which were 26.66 ± 6.05, 49.16 ± 6.43 and 26.66 ± 4.32. Conclution of this research was the addition of 0,05 % green tea extract can be used as a diluent could maintain the precentage of spermatozoa quality until 5 days after diluent.